What Role for the Spouse in a Voluntary Career Transition? Research Insights and Managerial Considerations - Grima, François; Meier, Olivier (International Transitions, 2024)
The purpose of this research is twofold. Firstly, we provide an overview of academic research on voluntary professional transition by recontextualizing it within the French context. Secondly, we emphasize the importance of spousal social support during this period of individual career questioning. We demonstrate the existence of a gap between the recognition of this contribution and the limited number of studies addressing it. We propose a research agenda by suggesting various promising research avenues.